Artificial intelligence: HR friend or foe?. Issue 2 (8th April 2019) - Hogg, Peter
Abstract : Purpose: While the use of artificial intelligence (AI) in the workplace is on the rise, few understand how it will affect our jobs. Will it be a hindrance? A threat? Or the solution to the current productivity dilemma? As with any new, and largely untested, technology, AI brings both challenges and opportunities that we need to be conscious of. Design/methodology/approach: The current and potential future implementation of AI technologies at Schneider Electric is assessed. Findings: In HR, it is our responsibility to help navigate business leaders towards making the best business decision, often with the use of technology. AI, like analytics before it, has huge potential. Originality/value: What we know for sure, is that the development of human talent has become one of the top priorities for global CEOs. With severe talent shortages in the UK, finding the right candidates for the job and investing in their professional development and well-being to keep them for longer look like no-brainers.